Ascaridiósis hepática y de las vías biliares. Estudio de cinco casos anatomo-clínicos - Céspedes, Rodolfo (1953)
We present five fatal cases of liver and bile ducts ascaridiasis with important lesions in thcse organs. These cases were obtained from a review of 1.633 autopsies; four of them were in children and one in adult. The intestinal ascaridiasis was mínimal, discret or intense. The four cases in children had an evolution with an acute process that of the adult had a cronic course. Only one of the five cases was diagnosed clinically. The outstanding clinical facts in this serie are: history of ascaridiasis or its recent therapy; an acute intestinal picture with diarrhea, fever, with or withont hepatomegaly and jaundice; with or without meningeal signes and normal spinal fluid. In two of the cases in which a differential count was done, it was found an absence of eosinophilic cells. The pathological findings of importancc were: intestinal oclusion, acute peritonitis, empyema of the gall-bladder, colangitis, hepatic abscess, adenomatous hyperplasis of the intra-hepatic ducts. We found worms underneath Glisson's capsule to a distance of 11 cm of the ampule of Vater; this in children's livers. We have considered that any fact which is capable of disturbing the life condition of the Ascaris lumbricoides in side tbe small intestine of the human, can predispose to their migration. From the anatomical point of view, we can accept. that the atony of the sphintcr of Oddi and dilatation of the biliary ducts can make an easy way to the ascense of the worm, although the anatomical structure of the valve of Heister would make difficult. The finding of the ascaris in the gall-bladder was less frcquent than their finding in the intra-hepatic biliary ducts. The related facts show us without doubt that the rural population of Costa Rica needs a strong and vigorous dosis of Sanitary Education and improvement of the living conditions.